Web-based internet security / Zuriani Karia - Zuriani, Karia (2003)
The proliferation in the use of Internet has led to the emergence of a series of security threats capable of compromising the integrity of the business data while impacting the availability of computers and business systems. So this internet Security Web-Based will be developed to provide an easy and convenient for every user around the world to know better about Internet Security. This system will allow users to access information just by clicking the mouse to have the best and complete information just from this website. This Internet Security web-based is a stand-alone system and will be developed with the objectives of utilizing the computer and information communication technology. There are two sections in this system where as user section and administrator section. The user section will be provided to any users to serach their information about internet security and the administrator section is provided to any users the registrered as an administrator and can have a lot of conveniences to upload data. This system also provides information about the potential attacks, Internet Security Issues, proposed solution and much more. It will be developed on the Windows 2000 Professional platform and utilizes Microsoft SQL Server as the database to store the information. This system also will be used HS web server and powerful tools for developing Internet contents, Visual InterDev 6.0 that offers more features of FrontPage. In order to build a very user-friendly web page, this system will be developed using scripting language technologies such as HTML, XHTML, JavaScript and also Active Server Pages. It is believed that the system will be created with proper environment to become the best web page that providing essential information about Internet Security.